Meningkatkan Prestasi Belajar PAKBP Siswa Kelas VIII Pada Materi Yesus Mewartakan Kerajaan Allah Model PBL Di SMP Negeri 2 Seluas - Benedikta Deta; Gea Mawarni; Agustinus Mulyono (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Catholic Religious Education (PAK) is one of the subjects taught in schools. Like every subject, Catholic Religious Education has its objectives. The aim is to build the competence of students as individuals of faith, to flourish and develop children into Christian individuals grounded in a relationship with Jesus Christ. This Catholic Religious Education subject should provide students with opportunities to be active as designed in the Independent Curriculum, which gives flexibility for educational units and teachers to develop their potential and freedom for students to learn according to their abilities and development. However, theoretical learning in Religious Education for class VIII at SMP Negeri 2 Seluas still often uses conventional learning methods. As a result, the learning outcomes of the subject have not yet reached the determined mastery target, and students' attitudes in learning are not apparent. Therefore, this study aims to (1) understand the application of the inquiry learning method, (2) improve the learning outcomes of Catholic Religious Education, and (3) enhance the religious attitude of class VIII students at SMP Negeri 2 Seluas using the Problem Based Learning method. PBL model also increases active participation and critical thinking skills of students in understanding and applying the concept of parables in the context of daily life.